Screening of Bacteria Producing Asparaginase Free of Glutaminase and Urease from Hot Springs in West Sulawesi - Ruby Setiawan; Dinar Rahmi Larasati (Biosaintifika: Journal of Biology & Biology Education, 2019)
L-asparaginase catalyzes the hydrolysis of asparagine into ammonia and aspartate. It has been used in chemotherapy for patients with acute lymphoblastic leukemia. L-asparaginase presents in animal, plant and microorganism. Long-term application of this enzyme can induce neurotoxicity due to the affinity towards glutamine and urea. The aim of this research was to find new source of glutaminase and urease-free asparaginase from bacteria. Bacteria were isolated from hot springs located in West Sulawesi using R2A media. The identification was employed by amplifying 16S rRNA gene. Screening of asparaginase was conducted using asparagine as single source of Nitrogen. Out of 21 isolates, 76% were Gram-negatives from the genus of Pseudomonas, Acinetobacter, Bosea, Caulobacter, Sphingomonas and Novosphingobium, while the rest of them were Gram-positives from the genus of Mycobacterium, Brachybacterium, Rhodococcus, and Staphylococcus. Twelve isolates which showed asparaginase activity were Caulobacter flavus HS1YWS2 and HS1XWS3, Acinetobacter sp. HS2XWS5, HS2XWS6, HS2XWS8, HS2YWS11, HS2YWS12, HS2YWS13, HS2ZWS14, HS2ZWS15 and HS2ZWS16. Isolates HS1YWS2 and HS1XWS3 were free of glutaminase and urease and showed the highest activity. This study was the first report of asparaginase activity from Caulobacter flavus. This result can further be used to explore the ability of asparaginase free of glutaminase and urease to treat acute lymphoblastic leukemia.